The Effect of Feature Convenience and Discounts on Post-Purchase Feelings in TikTok Shop among Generation Z - Alimah Alda Fuadiyah; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The rapid growth of social commerce has transformed online shopping behavior, particularly among Generation Z consumers. TikTok Shop, as a social commerce platform, integrates interactive features, seamless purchasing processes, and promotional incentives such as discounts and flash sales. This study aims to analyze the impact of feature convenience and discounts on post-purchase feelings, specifically post-purchase satisfaction and post-purchase regret, among Generation Z TikTok Shop users. A quantitative research design was employed using a survey method, with data collected from respondents who had made purchases on TikTok Shop within the last six months. The data were analyzed using a partial least squares based approach. The results indicate that perceived ease of use has a significant positive effect on post-purchase satisfaction, while discounts do not show a significant direct influence on satisfaction. Furthermore, neither feature convenience nor discounts were found to have a significant effect on post-purchase regret. These findings suggest that post-purchase satisfaction in social commerce is driven more by platform usability and user experience than by promotional incentives. Meanwhile, post-purchase regret appears to be influenced by other factors beyond the scope of this study. The findings provide practical implications for social commerce platform developers to prioritize usability and for consumer education initiatives aimed at promoting responsible digital consumption among Generation Z.